Celluloid Brutality: The Portrayal of Violence Against Women in Bangladeshi Cinema - Sabiha, Salma (The Jahangirnagar Review Part-C, 2024)
This study examines the portrayal of violence against women in Bangladeshi cinema through a qualitative analysis of four films: "Guerrilla" (2011), "Meherjaan" (2011), "Television" (2012), and "Rehana Maryam Noor" (2021). The study explores how such cultural representations resurface in films relative to gender-based violence within cultural and historical frameworks employing secondary data analysis enshrined by critical discourse examination. The findings reveal a significant evolution in how violence is portrayed: From reporting physical violence in overall movies to analyzing structural and psychological violence in some of the contemporary movies. The analysis identifies three key trends: (1) a shift from depicting women as passive victims to complex characters actively responding to violence, (2) an expansion in the portrayal of violence beyond physical abuse to include institutional and social forms of oppression, and (3) increasingly sophisticated cinematographic techniques that emphasize psychological impact over graphic representation. These changes are indicative of shifts in perceptions of gender-based violence more widely, and the function of cinema in relation to presenting social problems in present day Bangladesh. The research advances existing knowledge about gender depiction in South Asian movies and argues that changing visualizations of women in movies mirror and impact the culture of gendered violence.